2020
DOI: 10.5455/medarh.2020.74.58-60
|View full text |Cite
|
Sign up to set email alerts
|

Kinking of Bilateral Internal Carotid Arteries as Cause of Cognitive Dysfunction

Abstract: Introduction: Dolichoarteriopathies of the internal carotid artery (DICAs) is divided into three forms: tortuous, coiling and kinking. In case of kinking, internal carotid artery forms a sharp angle of <90 degrees, while in the background there is metaplasia of a tunica media with unknown etiology. The association with stroke is still questionable, but it is believed that it can be associated with cerebral ischemia and with clinical symptomatology that accompanies cerebral ischemia. Aim: Aim of article was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
(12 reference statements)
1
0
0
Order By: Relevance
“…It has been postulated that the variant led to decreased cerebral blood flow and cognitive decline. Kinking can also lead to syncope when the neck is turned abruptly, as was seen in our patient [11]. Del Corso L et al showed that patients with ICA abnormalities, including kinking, tortuosity, and coiling, have a low association with stroke or atherosclerotic vascular disease [12].…”
Section: Discussionsupporting
confidence: 62%
“…It has been postulated that the variant led to decreased cerebral blood flow and cognitive decline. Kinking can also lead to syncope when the neck is turned abruptly, as was seen in our patient [11]. Del Corso L et al showed that patients with ICA abnormalities, including kinking, tortuosity, and coiling, have a low association with stroke or atherosclerotic vascular disease [12].…”
Section: Discussionsupporting
confidence: 62%